Static and cyclic behavior of steel beams retrofitted with fiber reinforced polymer laminates - Yu, Yi (2009)
The rapid deterioration of aging steel infrastructures requires some significant attention in developing new techniques for effective and economical revival of these structures. External bonding of Fiber Reinforced Polymer (FRP) laminates is a promising method for strengthening such structures. This thesis presents a study on performance of FRP-steel joints and steel beams retrofitted with FRP under static and cyclic loading. Experiments on different types of FRP-steel adhesive joints were performed to have a fundamental understanding of the bond property and the adhesive failure behavior. Based on the experimental results, finite element (FE) analyses were conducted to explore in detail the stress and strain distribution along the bondline. Flexural behavior of steel beams strengthened or repaired with bonded FRP laminates under static loading was experimentally investigated. A simple analytical solution was developed for the flexural capacity of FRP strengthened steel beams. A bond failure model was proposed to predict bond failure load under static loading. The bond failure model can be incorporated into numerical modeling to simulate the static behavior of FRP strengthened steel beams with bond failure process. Parametric study was performed subsequently and the relationships between bond strength and different strengthening parameters were found out. Bond performance under cyclic loading of FRP-steel joints and FRP strengthened steel beams as well as fatigue strengthening effect of FRP laminates on damaged steel beams were explored in three series of experiments respectively. Failure modes, stress distribution and relationship between the load level and number of cycles to failure were observed and analyzed.